Keefektifan penggunaan mobile learning aplikasi HSK online untuk menunjang pengayaan kosakata Bahasa Mandarin di masa pandemi - Putri, Amira Eza Febrian; Ilana, Virlya Rahma (2020)
Mobile learning is e-learning using mobile devices. This research aims to find out the effectiveness of using HSK online applications to support the enrichment of Mandarin vocabulary of students of Malang University Chinese language education study program. The results of this study show that the Chinese HSK Online application can help students learn vocabulary. E-learning using HSK online application greatly helps the effectiveness of learning in the Covid-19 pandemic. This application can be an alternative to the utilization of technology used in the learning process.